The Jewish annotated New Testament new revised standard version Bible translation - Levine, Amy-Jill 1956-; Brettler, Marc Zvi 1958- (Oxford Oxford University Press, 2017)
"First published in 2011, The Jewish Annotated New Testament was a groundbreaking work, bringing the new Testament's Jewish background to the attention of students, clergy, and general readers. In this new edition, eighty Jewish scholars bring together unparalleled scholarship to shed new light on the text. This thoroughly revised and greatly expanded second edition brings even more helpful information and new insights to the study of the new Testament." -- Back cover
First published in 2011, The Jewish Annotated New Testament was a groundbreaking work, bringing the New Testament's Jewish background to the attention of students, clergy, and general readers. In this new edition, eighty Jewish scholars bring together unparalleled scholarship to shed new light on the text. This thoroughly revised and greatly expanded second edition brings even more helpful information and new insights to the study of the New Testament. * Introductions to each New Testament book, containing guidance for reading and specific information about how the book relates to the Judaism of the period, have been revised and augmented, and in some cases newly written. * Annotations on the text-some revised, some new to this edition-provide verse-by-verse commentary. * The thirty essays from the first edition are thoroughly updated, and there are twenty-four new essays, on topics such as "Mary in Jewish Tradition,", "Christology," and "Messianic Judaism." * For Christian readers The Jewish Annotated New Testament offers a window into the first-century world of Judaism from which the New Testament springs. There are explanations of Jewish concepts such as food laws and rabbinic argumentation. It also provides a much-needed corrective to many centuries of Christian misunderstandings of the Jewish religion. * For Jewish readers, this volume provides the chance to encounter the New Testament-a text of vast importance in Western European and American culture-with no religious agenda and with guidance from Jewish experts in theology, history, and Jewish and Christian thought. It also explains Christian practices, such as the Eucharist. The Jewish Annotated New Testament, Second Edition is an essential volume that places the New Testament writings in a context that will enlighten readers of any faith or none. Review: An admirable piece of scholarship... Much contemporary writing on Scripture is faddish or tendentious. This book is a disciplined work of clarification and illumination. * Marilynne Robinson, Wall Street Journal * Praise for the first edition: "A magnificent achievement... The Jewish Annotated New Testament is a marvelously bounteous compilation." * Commonweal *
Paul in Jewish thought Daniel R. Langton.
The New Revised Standard Version Bible translation is based "on the most recent edition of the Greek New Testament ... published by the United Bible Societies (1966)" -- page xvii
Keywords: Bible -- Commentaries; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc., Jewish; Judaism; Jews in the New Testament; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Bible; Christianity and other religions; Jews in the New Testament; Judaism